Consumption patterns of Sugar Sweetened Beverages (SSB) and its relationship with the risk of excess sugar intake among adolescents - Lirista Dyah Ayu Oktafiani; Nur Fitri Widya Astuti; Farida Wahyu Ningtyias (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
The adolescent age group had a tendency to have an unhealthy diet, such as consuming more sugar (53,1%) than the other age groups. The increasing consumption of sugar-sweetened beverages (SSBs) is a major contributor to the increasing prevalence of obesity in adolescents in Indonesia. Increased consumption of SSB in adolescents is thought to be one of the factors contributing to the increase in obesity prevalence. Jember Regency as one of the areas with modern lifestyle trends shows a trend of consumption of these drinks that needs to be analyzed in more depth. The purpose of this study was to analyze the consumption patterns of SSB in adolescents and the relationship between the characteristics of respondents and the type, amount, and frequency of SSB consumption. This was an analytical observational study with a cross-sectional design. The study was conducted from June to September 2024. The independent variables of the study consisted of respondent characteristics, including gender, age, and education, while the dependent variable was the consumption pattern of sugar-sweetened beverages in packaging (SSB), including the type, size, amount, and frequency of SSB consumption. Data collection on SSB consumption patterns in adolescents was carried out with an instrument in the form of a semi-quantitative food frequency (SQ-FFQ) questionnaire online using the Google form. The research data were analyzed univariately and bivariately using the chi-squared test. The results showed that almost all respondents (97,75%) consumed more than one type of SSB. Tea type SSB (37,39%) was the most consumed/favored, with a frequency of consumption of 2-3x/week by (48%). In addition, the absence of significant differences in the consumption patterns of SSB in terms of the type of SSB consumed and the characteristics of respondents indicates that SSB is favored by adolescents with a fairly high frequency, regardless of differences in individual characteristics.